Cytomegalovirus reactivation is associated with a lower rate of early relapse in myeloid malignancies independent of in-vivo T cell depletion strategy. (June 2017) - Hilal, Talal; Slone, Stacey; Peterson, Shawn; Bodine, Charles; Gul, Zartash
Highlights: CMV reactivation is associated with lower rate of relapse in myeloid malignancies. Non-relapse mortality appeared to be higher in patients with CMV reactivation. Both alemtuzumab and ATG have similar effects on CMV reactivation and overall survival. Abstract: The association between cytomegalovirus (CMV) reactivation and relapse risk has not been evaluated in relation to T cell depletion strategies. We evaluated 93 patients who underwent allogeneic hematopoietic stem cell transplantation (HSCT) and analyzed the association between T cell depletion strategies with the cumulative incidence of relapse and CMV reactivation. A total of 33% of patients who received ATG vs. 34% who received alemtuzumab developed CMV reactivation. The cumulative incidence of relapse was 3% at 1 year and 20% at 3 years in patients with CMV reactivation vs. 30% at 1 year and 38% at 3 years in patients without CMV reactivation (p = 0.02). When analyzed separately, this effect persisted in the myeloid, but not the lymphoid group. There was a numerical trend towards increased non-relapse mortality (NRM) in patients with CMV reactivation, especially in the myeloid group. The choice of T cell depleting agent and the rate of CMV reactivation were not associated with different overall survival (OS) rates. These results suggest that the choice of T cell depletion strategy may have similar effects on rates of CMV reactivation, disease relapse, and survival. Further studies examining these variables in patients not exposed to in-vivo T cell depleting agents may be of interest.